The role of unsustainable HR practices as illegitimate tasks in escalating the sense of workplace ostracism - Ahmad, Afaq; Zhao, Chenhui; Ali, Ghazanfar; Zhou, Kunshun; Iqbal, Jawad (Frontiers in Psychology, 2022)
Unsustainable HR practices impose illegitimate tasks on employees due to shortage of resources. These illegitimate tasks bring counterproductive work behaviour in terms of workplace incivility that creates the sense of ostracism in employees. To address these issues, the study examined the relationship among unsustainable HR practices in terms of illegitimate tasks and workplace ostracism. Whereas workplace incivility is defined as an underlying reason through which this association exist. Adopting a theoretical framework from earlier researches, the study used cross-sectional data and subsequent a method of quantitative research, the sample comprised permanent faculty members of private universities in Pakistan working in different departments with different role titles. Smart PLS was applied to run multiple statistical analysed on the obtained data. The results from the study supported hypothesis by depicting a positive and significant association among illegitimate tasks and workplace ostracism. Further, workplace incivility was playing the mediating role among illegitimate tasks and workplace ostracism. The results from the study carry significant implications for managers and researchers. Recommendations and future research directions are also discussed in the paper.